2002
DOI: 10.1034/j.1600-0897.2002.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Dominant IL‐10 and TGF‐β mRNA Expression in γδT Cells of Human Early Pregnancy Decidua Suggests Immunoregulatory Potential

Abstract: The present findings suggest that gammadeltaT cells in normal pregnancy create a cytokine milieu promoting immunotolerance to the fetus. We hypothesize that through the production of the immunosuppressive cytokines IL-10 and/or TGF-beta the gammadeltaT cells could function directly as regulatory T cells or induce the differentiation of Th0 TCRalphabeta+ cells into regulatory/suppresser cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 40 publications
5
128
0
3
Order By: Relevance
“…These data are in agreement with those from other research groups (10, 17). Moreover, IL-10 levels were significantly diminished and TGF-␤ levels were slightly diminished in pathological pregnancies compared with normal pregnancies, further suggesting low Treg numbers in pathological pregnancies, since Treg are known to affect immune responses by secreting antiinflammatory cytokines at the fetal-maternal interface (14,61,67). Thus, our data on low levels of hCG coinciding with low levels of Treg-associated molecules suggest that hCG may be chiefly responsible for Treg attraction to the fetal-maternal interface.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These data are in agreement with those from other research groups (10, 17). Moreover, IL-10 levels were significantly diminished and TGF-␤ levels were slightly diminished in pathological pregnancies compared with normal pregnancies, further suggesting low Treg numbers in pathological pregnancies, since Treg are known to affect immune responses by secreting antiinflammatory cytokines at the fetal-maternal interface (14,61,67). Thus, our data on low levels of hCG coinciding with low levels of Treg-associated molecules suggest that hCG may be chiefly responsible for Treg attraction to the fetal-maternal interface.…”
Section: Discussionmentioning
confidence: 66%
“…The suppressive function of Treg is mediated either via cell-cell contact (11) or by secretion of immunosuppressive cytokines such as IL-10 and TGF-␤ (12)(13)(14)(15)(16). Additionally, it has been demonstrated that the proportion of decidual Treg was significantly lower in specimens from spontaneous abortion compared with those from induced abortions (10).…”
Section: Cd25mentioning
confidence: 99%
“…Human Vd1 T cells have been observed to be recruited to the maternal/fetal interface during pregnancy where their activation is believed to play a role in the induction of tolerance to paternal antigens. 15,[51][52][53][54] Furthermore, there is evidence suggesting that the early pregnancy human decidua is actually a site of extrathymic maturation of Vd1 T cells. 55,56 This enrichment of cd T cells at the maternal/fetal interface and their mysterious role in pregnancy is not unique to humans as the same has been observed in sheep 57 and mice 58 , suggesting a central conserved role of cd T cells involved in pregnancy-related immune changes.…”
Section: Missingmentioning
confidence: 99%
“…After incubation, total RNA was isolated and cDNA transcribed as previously described (27). Real-time quantitative RT-PCR was performed with specific primers and probes for perforin as described below.…”
Section: Analysis Of the Effect Of Nkg2d Ligand-expressing Placental mentioning
confidence: 99%
“…Total RNA and cDNA were obtained from laser microdissected and isolated STB and from purified lymphocyte subpopulations incubated in the presence or absence of exosomes. ULBPs were amplified from STB cDNA and perforin from NK, CD8 ϩ , and ␥␦ T cell cDNA on ABI PRISM 7700 by TaqMan Gene Expression Plate (I) protocol (PE Applied Biosystems) as described (27). Primer and probe sequences, detecting all five ULBP members, were as follows: ULBP1/RAET1I (forward) 5Ј-GATCCAACAAAACCACCCTC TCT, (reverse) 5Ј-ACTTTCCACCTGTCACTCTAAACAAC, (probe) 5Ј-TGGCCACCACCCTCAGTCCCTG; ULBP2/RAET1H (forward) 5Ј-AG GAGCACCACTCGCCAT, (reverse) 5Ј-AGGAGCCTTTTGGTATCAGC TT, (probe) 5Ј-TGCTTCATCCTCCCTGGCATCTGA; ULBP3/RAET1N (forward) 5Ј-CACAGCACCACCCACCAT, (reverse) 5Ј-TCACCTTCCA CCTGTCACTCTAA, (probe) 5Ј-TGCTTCATCCTCCCTGGCATCTGA; ULBP4/RAT1E (forward) 5Ј-CTGCAAGTCGAGATGTTTTGTCA, (reverse) 5Ј-AAAGAGGAGGGATTTCTCTCCAT, (probe) 5Ј-TGCACTGG TGCATCCTGGCAGTT; and ULBP5/RAET1G (forward) 5Ј-CACAGT CTGACCCAAAGCCA, (reverse) 5Ј-GGTAGCTGTCACTCCAAAGGAC TC, (probe) 5Ј-TGGCCACCACCCTCAGTCCCTG.…”
Section: Dna and Total Rna Extraction And Quantitative Real-time Pcr mentioning
confidence: 99%